2005
DOI: 10.1071/rd05005
|View full text |Cite
|
Sign up to set email alerts
|

Fertility aspects in yearling beef bulls grazing endophyte-infected tall fescue pastures

Abstract: During a 2-year study, yearling beef bulls were used to determine the effects of grazing on endophyte-infected tall fescue on endocrine profiles, semen quality and fertilisation potential. Bulls were allotted to graze tall fescue pastures infected with Neotyphodium coenophialum (E+; n = 20 per year) or Jesup/MaxQ (Pennington Seed, Atlanta, GA, USA; NTE; n = 10 per year). Bulls were grouped by scrotal circumference (SC), bodyweight (BW), breed composites and age to graze tall fescue pastures from mid-November u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Changes in sperm quality between bulls grazing toxic EI or NE fescue pastures were detected only after ambient temperatures increased in July and August. Differences between Schuenemann et al (2005a) and the current study also may be attributed to laboratory methodologies; Schuenemann et al (2005a) used subjective procedures, whereas an IVOS analysis was used in the current experiment. Sperm motility of Holstein bulls ranged from 62 to 69% with subjective procedures, whereas the range was 52 to 82% for computer-assisted sperm analysis; repeatability was 0.99 for computer-assisted sperm analysis (Farrell et Major defects = malformed, abnormal acrosome, proximal droplet, folded tail, midpiece defect, cratered head, pyriform head, or small/giant head.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Changes in sperm quality between bulls grazing toxic EI or NE fescue pastures were detected only after ambient temperatures increased in July and August. Differences between Schuenemann et al (2005a) and the current study also may be attributed to laboratory methodologies; Schuenemann et al (2005a) used subjective procedures, whereas an IVOS analysis was used in the current experiment. Sperm motility of Holstein bulls ranged from 62 to 69% with subjective procedures, whereas the range was 52 to 82% for computer-assisted sperm analysis; repeatability was 0.99 for computer-assisted sperm analysis (Farrell et Major defects = malformed, abnormal acrosome, proximal droplet, folded tail, midpiece defect, cratered head, pyriform head, or small/giant head.…”
Section: Discussionmentioning
confidence: 92%
“…In the current experiment, percentage of rapid progressive sperm was decreased in EI compared with NE bulls in July and August. Schuenemann et al (2005a) reported that although sperm motility and morphology did not differ between bulls grazing toxic EI or NE fescue pastures from November to June, potential of sperm to fertilize oocytes was reduced from bulls grazing toxic EI fescue. Similarly, we did not detect differences in sperm motility in May and June.…”
Section: Discussionmentioning
confidence: 98%
“…The toxins produced by many cultivars of tall fescue containing mutualistic endophytes are ergot alkaloids and are potent dopaminergic agonists. Consumption of ergot alkaloids clearly suppresses serum PRL concentrations in bulls [30,31,40,46]. Prolactin is known to be present in the human seminal fluid [13,14], so we evaluated its presence and determined if the levels of PRL in seminal fluid were impacted by the consumption of ergot alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive effects have been noted in several species consuming E+ tall fescue, including mice, rabbits, horses, sheep, and cattle (Daniels et al, 1984;Boling, 1985;Zavos et al, 1987;Bond et al, 1988;Monroe et al, 1988;Porter and Thompson, 1992;Jones et al, 2003;Schuenemann et al, 2005). Ruminants typically have reduced conception rates and, thus, reduced reproductive efficiency.…”
Section: Reproductionmentioning
confidence: 99%